Smallpox vaccination in a mouse model - S. N. Shchelkunov; A. A. Sergeev; S. A. Pyankov; K. A. Titova; S. N. Yakubitskiy (Вавиловский журнал генетики и селекции)
The monkeypox epidemic, which became unusually widespread among humans in 2022, has brought awareness about the necessity of smallpox vaccination of patients in the risk groups. The modern smallpox vaccine variants are introduced either intramuscularly or by skin scarification. Intramuscular vaccination cannot elicit an active immune response, since tissues at the vaccination site are immunologically poor. Skin has evolved into an immunologically important organ in mammals; therefore, intradermal delivery of a vaccine can ensure reliable protective immunity. Historically, vaccine inoculation into scarified skin (the s.s. route) was the first immunization method. However, it does not allow accurate vaccine dosing, and high-dose vaccines need to be used to successfully complete this procedure. Intradermal (i.d.) vaccine injection, especially low-dose one, can be an alternative to the s.s. route. This study aimed to compare the s.s. and i.d. smallpox immunization routes in a mouse model when using prototypic second- and fourth-generation low-dose vaccines (104 pfu). Experiments were conducted using BALB/c mice; the LIVP or LIVP-GFP strains of the vaccinia virus (VACV) were administered into the tail skin via the s.s. or i.d. routes. After vaccination (7, 14, 21, 28, 42, and 56 days post inoculation (dpi)), blood samples were collected from the retro-orbital venous sinus; titers of VACV-specific IgM and IgG in the resulting sera were determined by ELISA. Both VACV strains caused more profound antibody production when injected via the i.d. route compared to s.s. inoculation. In order to assess the level of the elicited protective immunity, mice were intranasally infected with a highly lethal dose of the cowpox virus on 62 dpi. The results demonstrated that i.d. injection ensures a stronger protective immunity in mice compared to s.s. inoculation for both VACV variants.